19 Livestreaming from smartphones to the dispatch center in real emergency calls. (26th April 2019) - Linderoth, G; Østergaard, D; Fjordholt, M; Folke, F; Lippert, F
Abstract : Background: Currently, the emergency medical dispatchers rely solely on the spoken word when assessing and triaging emergency calls. We aimed to explore if livestreaming by bystanders could be useful during emergency calls. Method: In a 3 months period, livestreaming could be added to the emergency call at the Emergency Medical Services, Copenhagen. Nine medical dispatchers were trained to instruct laypersons to ad livestreaming at a 1 day simulation-based course before the period. For livestreaming caller received a text message with a link. When activating the link, the smartphone camera opened, allowing video to be streamed encrypted to the dispatcher. GoodSAM provided the technical solution. Results: In 68 cases, the caller had a smartphone and the dispatcher suggested livestreaming which succeeded in 33 cases. Reasons for no livestreaming were refusal from bystander (n=6) or patient (n=2), text message not received before ambulance arrival (n=17), and technical issues or caller skills (n=11). The dispatchers found the live video recording useful in all cases. In 8 cases (24%) the patient was considered more critical ill when livestreaming was added, whereas in 8 (24%) cases the patient was considered less sick. Change in ambulance priority response was done in 3 cases after the dispatchers had video. Among 25 callers interviewed 22 experienced livestreaming as an advantage. Conclusion: Adding video livestreaming to the emergency call seems useful for the medical dispatchers to improve patient assessment and to provide the appropriate emergency response. The callers found livestreaming an advantage. Technical issues/experiences, however, need to be improved. Conflict of interest: The authors declare that they have no competing interests. Funding: Emergency Medical Services Copenhagen: has received unrestricted research grants from the Laerdal Foundation for acute medicine and from the Danish foundation TrygFonden. CAMES has received unrestricted research grants from the Laerdal Foundation.